GERAKAN 1000 MASKER : PEMBAGIAN MASKER KEPADA YAYASAN KAKAK ASUH BALI KARANGASEM - Ni Kadek Yuni Utami (Jurnal Lentera Widya, 2020)
The outbreak of the Covid19 virus has impacted the world. In Indonesia, 3.512 people are infected as of April 10, 2020. One of the WHO's advice on the use of masks for the community, was supported by Ministry of Tourism and Creative Economy (Kemenparekraf) with Gerakan Masker Kain ( Cloth Mask Movement). Many people in Indonesia do not understand the importance of using masks, and it makes STD Bali held Gerakan 1000 Masker (1000 Masks Movement ) with students and lectures involved in production and distribution in several areas in Bali. Gerakan 1000 Masker is important considering that not many people have the awareness and education to use masks against the Covid19 outbreak. Gerakan 1000 Masker Sekolah Tinggi Desain Bali, were carried out in several areas and foundations such as Yayasan Kakak Asuh Bali Karangasem on April 20, 2020 with the aim of giving masks to underprivileged children in Karangasem and raising their awareness together against Covid19 outbreak.